2022
DOI: 10.1210/jendso/bvac002
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Cognition Among Hypoparathyroid Adults

Abstract: Purpose Hypoparathyroid patients describe cognitive deficits, yet data regarding objective assessment of cognitive function are limited. We assessed cognition in a pilot study of hypoparathyroid patients using the NIH Toolbox® Adult Cognitive Battery (NIHTB-CB). We also sought to determine whether cognition relates to emotion, quality of life (QoL) and hypoparathyroidism-related biochemistries. Methods Nineteen hypoparathyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Moreover, a novel neuropsychological approach, using expert neuropsychologist-devised tests, has allowed the analysis of cognitive, executive, and attentive functions in patients with Hypoparathyroidism. Patients with both idiopathic and post-surgical Hypoparathyroidism present neuropsychological impairment, with a worse performance in these tests for the former and for patients with longer follow-up and lower calcium levels, as evaluated in studies by our group and others [9,10,81].…”
Section: Pth and Brain: Evidence From Clinical Settingsmentioning
confidence: 69%
“…Moreover, a novel neuropsychological approach, using expert neuropsychologist-devised tests, has allowed the analysis of cognitive, executive, and attentive functions in patients with Hypoparathyroidism. Patients with both idiopathic and post-surgical Hypoparathyroidism present neuropsychological impairment, with a worse performance in these tests for the former and for patients with longer follow-up and lower calcium levels, as evaluated in studies by our group and others [9,10,81].…”
Section: Pth and Brain: Evidence From Clinical Settingsmentioning
confidence: 69%
“…Considering its psychological effects, hypoparathyroidism, which affects the quality of life, is evaluated from a broader perspective with current studies. In a pilot study, it was even shown that the cognitive functions of hypoparathyroidism patients were weakened Introductory Chapter: A Brief Statement about Parathyroid Glands DOI: http://dx.doi.org/10.5772/intechopen.110125 [18]. More studies are urgently needed to prevent hypoparathyroidism from the very beginning.…”
Section: Concernsmentioning
confidence: 99%
“…Limited reports have documented impaired cognitive function in nonsurgical hypoparathyroid patients, including reduced inhibitory control or an inability to suppress a thought, action, or feeling or a lack of “self-control,” impairment in visuo-spatial functioning, and psychomotor retardation [ 6 ]. In postsurgical hypoparathyroidism, the scant available data are variable, with one small study of predominantly White women showing impaired cognition, particularly slowed processing speed [ 7 ], and another report not finding a difference from controls but demonstrating that lower serum calcium levels were associated with worse visuo-spatial attention, executive function, and semantic memory scores [ 8 ]. Integrating hypoparathyroid patients' points of view is necessary to ascertain whether more studies are needed with formally administered cognitive testing by trained neuropsychologists.…”
mentioning
confidence: 99%